2022
DOI: 10.1590/fst.91221
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical content and antioxidant activity of extruded products made from yellow corn supplemented with apple pomace powder

Abstract: The aimed of this study was quantified total phenols content, total flavonoids, and antioxidant activity in extruded ready-to-eat products made from yellow corn added with apple pomace powder. A central composite rotatable experimental design was used. The variables tested were exit die temperature (140-180 °C), feed moisture (14-20 g/100 g) and apple pomace concentration (0-30 g/100 g). The effect of the process variables on the total contents of phenols, flavonols, flavanols and flavonoids and antioxidant ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The addition of apple pomace to these extrudates resulted in a 2-fold to 12-fold increase in flavonoids relative to control. Leon et al [ 23 ] also confirmed an increase in polyphenols in extruded products with yellow corn supplemented with apple pomace powder and a significant increase in flavonoids ranging from 15 to 200% relative to the control.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…The addition of apple pomace to these extrudates resulted in a 2-fold to 12-fold increase in flavonoids relative to control. Leon et al [ 23 ] also confirmed an increase in polyphenols in extruded products with yellow corn supplemented with apple pomace powder and a significant increase in flavonoids ranging from 15 to 200% relative to the control.…”
Section: Resultsmentioning
confidence: 89%
“…The addition of apple pomace to these extrudates resulted in a 2-fold to 12-fold increase in flavonoids relative to control. Leon et al [23] also confirmed an increase in polyphenols in extruded products with yellow corn supplemented with apple pomace powder and a significant increase in flavonoids ranging from 15 to 200% relative to the control. Analyzing the phenolic profile of corn extrudates with a share of apple pomace by UPLC-PDA-MS/MS method, it could be observed that even the control obtained from corn grits (sample EI CONTROL) contains high level of phenolic acids, which are partially endogenous acids originating from corn, namely, caffeoylglycerol, p-coumaroylquinic acid, 2-Op-coumaroylglycerol, and feruloylquinic acid, which due to the applied processing parameters are freed from the cell walls of the cereal, which is why their level in the sample is high.…”
Section: Corn Snacks Enriched With Apple Pomace As a Matrix Ofmentioning
confidence: 85%
See 3 more Smart Citations